Analisis Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan dengan Motivasi sebagai Variabel Intervening pada Karyawan WFH - Sandra, Novi; Sentoso, Antony (https://jurnal.binamandiri.ac.id/, 2024)
In an increasingly tight business competition era, employee performance is the key for companies to achieve their goals. This research investigates the influence of compensation, work discipline, and motivation on employee performance in manufacturing companies that implement Work from Home (WFH) in Batam City. This research also examines whether motivation can act as a mediating variable in the relationship between compensation discipline and employee performance. Data was collected by distributing questionnaires to 270 respondents who were WFH employees in Batam City. The research results show that work compensation and work discipline do not significantly influence employee performance. However, work motivation has a significant favorable influence on employee performance. Work motivation also acts as a mediating variable between work compensation, work discipline, and employee performance.